The problem of hyperammoniemia after orthotopic liver transplantation - S. V. Zhuravel; P. Yu. Falevko; V. A. Manukovskiy; M. E. Malyshev (Трансплантология (Москва), 2025)
Background. Currently, there is no doubt that orthotopic liver transplantation increases life expectancy compared to standard treatment methods in patients with decompensated liver cirrhosis. In recent years, diagnostics and treatment of hyperammonemia have attracted increasing attention in various liver diseases, and also after liver transplantation. At the same time, there are few studies with a high level of evidence establishing a relationship between the blood level of ammonia and the severity of patient condition in the early period after liver transplantation.Objective. To summarize current data on the problem of hyperammonemia after liver transplantation, to analyze the mechanisms of appearing high ammonia concentrations in blood serum and their pathogenetic role in the development of complications after orthotopic liver transplantation, and also to investigate the methods for monitoring the blood ammonia levels.Material and methods. The analysis of data from world experimental and clinical studies on the pathogenesis, diagnostics, and treatment methods of hyperammonemia after orthotopic liver transplantation has been made. The literature search was conducted in international databases (PubMed/MedLine, ResearchGate), as well as in the scientific electronic library of Russia (eLIBRARY.RU) for the period from 2019–2024.Conclusion. In the analyzed publications, the issues on the problem of hyperammonemia after liver transplantation are worthwhile to be addressed to. Despite advances in understanding the pathogenesis of hyperammonemia and its impact on the development of hepatic encephalopathy and disorders on the part of other body organs and systems, many unresolved issues remain both in diagnosis and in choosing the most effective treatment methods.